Hydrogel for DC current application and hydrogel sheet for DC current application
By integrating clay minerals with ion exchange ability into the hydrogel composition, the hydrogel maintains stable voltage and resistance against electrolysis, addressing the issue of conductivity degradation in direct current applications.
Patent Information
- Application Number
- JP2023105881
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-17
AI Technical Summary
Existing hydrogels used for direct current applications experience significant voltage changes due to electrolysis, leading to decreased conductivity over time.
Incorporation of clay minerals, particularly those with ion exchange ability, into the hydrogel composition to stabilize voltage and minimize electrolysis effects, combined with a specific polymer matrix and electrolyte content, results in a hydrogel with a voltage change rate of 10% or less when subjected to a direct current for 15 minutes.
The hydrogel maintains stable voltage and resistance values over time, ensuring effective conductivity and adhesiveness for prolonged direct current applications.
Smart Images

Figure 2025005633000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogel to which a direct current can be applied and a hydrogel sheet to which a direct current can be applied. [Background technology]
[0002] Hydrogels are both adhesive and conductive, and are therefore used in a wide range of fields as components of electrode pads that are attached to the body, wound dressings, and other materials. Hydrogels are sometimes used in direct current treatments, such as in a direct current bioelectrical treatment device (Patent Document 1) and in non-invasive brain stimulation methods that pass direct current, such as transcranial direct current stimulation (tDCS) (Patent Document 2). Since direct current has a stronger therapeutic effect than alternating current, there is a need for hydrogels that are suitable for application of direct current.
[0003] Patent Document 1 discloses a conductive laminated hydrogel sheet having at least two hydrogel sheet layers, in which a hydrogel sheet A layer having a thickness of a mm and a hydrogel sheet B layer having a thickness of b mm are alternately laminated, the hydrogel sheet A layer contains at least one inorganic salt in a total content of X% by weight relative to the total weight of the hydrogel sheet A layer, and the hydrogel sheet B layer contains at least one inorganic salt in a total content of Y% by weight relative to the total weight of the hydrogel sheet B layer, where Y is less than X, and the hydrogel sheet B layer contains at least one acid.
[0004] Patent Document 2 discloses an electroencephalogram measuring and brain stimulation system including a first electrode unit for applying a microcurrent to stimulate the brain and a second electrode unit for measuring an electroencephalogram received from the brain, the second electrode unit including a cut filter for blocking the microcurrent. The electrolyte layer of the first electrode unit is made of a hydrogel layer containing an electrolyte.
[0005] When a hydrogel contains an inorganic salt as an electrolyte, electrolysis may occur inside the gel when a direct current is applied for a certain period of time. As the electrolysis progresses with the passage of time, the voltage value increases and the conductivity decreases. In Patent Document 1, two hydrogel sheet layers with different inorganic salt contents within a predetermined range are alternately laminated to suppress the increase in pH and the decrease in conductivity when a direct current is applied for a certain period of time. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-51155 A [Patent Document 2] Special Publication No. 2017-502722 Summary of the Invention [Problem to be solved by the invention]
[0007] The problem to be solved by the present invention is to provide a hydrogel for applying direct current and a hydrogel sheet for applying direct current which show little change in voltage value when a direct current is applied for a certain period of time. [Means for solving the problem]
[0008] The present invention encompasses the embodiments described below. Section 1. A hydrogel for applying direct current, which contains a clay mineral, and which exhibits a voltage change rate of 10% or less when a direct current of 2 mA is applied to it for 15 minutes. Section 2. Item 2. The hydrogel according to item 1, wherein the content of the clay mineral is 0.60 to 15.0 parts by mass per 100 parts by mass of the hydrogel. Section 3. Item 2. The hydrogel for application of direct current according to Item 1, wherein the clay mineral is an inorganic substance having ion exchange capacity. Section 4. Item 4. The hydrogel for applying a direct current according to Item 3, wherein the inorganic substance having ion exchange capacity is zeolite. Section 5. Item 2. The hydrogel according to item 1, having a thickness of 0.60 mm to 3.0 mm. Section 6. Item 2. The hydrogel for application of direct current according to Item 1, wherein the hydrogel comprises a polymer matrix, water, a polyhydric alcohol, and an electrolyte, and the polymer matrix is a copolymer of one or more monofunctional monomers selected from a (meth)acrylamide monomer and a (meth)acrylic acid ester, and a crosslinkable monomer. Section 7. Item 7. A hydrogel sheet for applying direct current, which is obtained by molding the hydrogel for applying direct current according to any one of items 1 to 6. Section 8. Item 8. The hydrogel sheet for applying a direct current according to Item 7, which has a thickness of 0.60 mm to 3.0 mm. Section 9. Item 7. A medical electrode hydrogel used by being placed between an electrode made of a conductive material and a skin surface, the medical electrode comprising the hydrogel for applying direct current according to any one of items 1 to 6. Section 10. Item 8. A biological electrode pad comprising the hydrogel sheet for applying direct current according to item 7 and an electrode electrically connected to the hydrogel sheet for applying direct current. Section 11. Item 7. A method for producing a hydrogel for applying a direct current according to any one of items 1 to 6, comprising: producing a hydrogel having a peak intensity of 50 to 150 mW / cm in a polymerizable solution containing an acrylic monomer, a crosslinkable monomer, water, a polyhydric alcohol, an electrolyte, and a clay mineral. 2 13. A method for producing a hydrogel, comprising the step of irradiating a hydrogel with ultraviolet light. Section 12. A hydrogel-forming composition for application of direct current, comprising an acrylic monomer, a crosslinkable monomer, water, a polyhydric alcohol, an electrolyte, and a clay mineral. Effect of the Invention
[0009] According to the present invention, it is possible to provide a hydrogel for applying a direct current and a hydrogel sheet for applying a direct current, which exhibit little change in voltage value even when a direct current is applied for a certain period of time. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view of a hydrogel sheet according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of a hydrogel sheet according to another embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view of an electrode pad according to an embodiment. [Figure 4] FIG. 11 is a schematic cross-sectional view of an electrode pad according to another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As used herein, "(meth)acrylate" means acrylate and / or methacrylate, "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid, "(meth)acryloyl" refers to acryloyl and / or methacryloyl, and "(meth)acrylamide" refers to acrylamide and / or methacrylamide.
[0012] In this specification, a "sheet" refers to a layered body having a thickness of 200 μm or more, and a "film" refers to a layered body having a thickness of less than 200 μm.
[0013] In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with a value shown in an example or a value that can be unambiguously derived from an example. Furthermore, in this specification, a numerical value connected with "~" means a numerical range that includes the numerical values before and after "~" as the lower and upper limits.
[0014] Hydrogel The hydrogel (hereinafter simply referred to as "hydrogel" or "gel") of an embodiment of the present invention is a hydrogel for application of direct current that contains a clay mineral, and has a voltage change rate of 10% or less when a direct current of 2 mA is applied for 15 minutes.
[0015] The hydrogel of an embodiment of the present invention contains clay minerals, which suppresses changes in voltage value due to electrolysis of inorganic salts and / or water when a direct current is applied to the hydrogel, and satisfies the characteristic that the voltage change rate when a direct current of 2 mA is applied for 15 minutes is 10% or less.
[0016] The content of the clay mineral in the hydrogel is not particularly limited as long as it is within the range that can suppress the voltage change rate, but in terms of effectively suppressing the voltage change rate while maintaining the function of the hydrogel, it is preferably 0.60 to 15.0 parts by mass, and more preferably 1.0 to 10.0 parts by mass, per 100 parts by mass of the hydrogel.
[0017] The clay mineral is preferably a clay mineral having an ion exchange ability, more preferably an inorganic substance having an ion exchange ability. When the clay mineral has an ion exchange ability, the application of a direct current to the hydrogel causes an exchange of chloride ions and hydrogen ions generated by electrolysis of inorganic salts and / or water in the hydrogel with ions in the clay mineral, thereby suppressing an increase in voltage.
[0018] Examples of clay minerals include, but are not limited to, zeolite, kaolinite, halloysite, smectite, mica clay minerals, vermiculite, chlorite, imogolite, allophane, sepiolite, varigorskite, gibbsite, hydrotalcite, etc. These clay minerals are inorganic substances having ion exchange capacity. From the viewpoints of the degree of suppression of changes in voltage value and the ease of adjusting the balance between hydrophilicity and hydrophobicity, the clay mineral is preferably zeolite.
[0019] The hydrogel according to an embodiment of the present invention contains a polymer matrix, which is a copolymer of a monofunctional monomer and a crosslinkable monomer.
[0020] The content of the polymer matrix in the hydrogel is preferably within the range of 5.0% to 50% by mass, more preferably 10% to 40% by mass, and even more preferably 13% to 35% by mass.
[0021] The monofunctional monomer is preferably an acrylic monomer. Acrylic monomers are a general term for monomers that have an acryloyl group (HC=CH-C(=O)-) or a methacryloyl group (HC=C(CH)-C(=O)-) and can be polymerized to form a polymer. Acrylic monomers are monofunctional monomers that have one polymerizable carbon-carbon double bond in the molecule and are non-crosslinking monomers.
[0022] The acrylic monomer is not particularly limited, but includes (meth)acrylamide monomers, (meth)acrylic acid esters, and (meth)acrylic acid. One or more selected from the (meth)acrylamide monomers and (meth)acrylic acid esters are preferred, and the (meth)acrylamide monomers are more preferred.
[0023] Specific examples of (meth)acrylamide monomers include (meth)acrylamide; N,N-dialkyl (meth)acrylamides such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; N-alkyl (meth)acrylamides such as N-isopropyl (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide and N-propyl (meth)acrylamide; N-hydroxyalkyl (meth)acrylamides such as N-hydroxyethyl (meth)acrylamide and N-hydroxymethyl (meth)acrylamide; N-ethoxymethyl (meth)acrylamide, N-propoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide and N-propyl (meth)acrylamide; Examples of the compound include N-alkoxyalkyl (meth)acrylamides such as butoxymethyl (meth)acrylamide, N-pentoxymethyl (meth)acrylamide, N-hexyloxymethyl (meth)acrylamide, N-heptoxymethyl (meth)acrylamide, N-octoxymethyl (meth)acrylamide, N-ethoxyethyl (meth)acrylamide, N-propoxyethyl (meth)acrylamide, and N-butoxyethyl (meth)acrylamide; cationic acrylamide compounds containing an amino group such as dimethylaminopropyl (meth)acrylamide; anionic acrylic monomers containing a sulfonic acid group or salts thereof such as 4-acryloylmorpholine and tert-butylacrylamidosulfonic acid; and derivatives thereof. Among these, one or more selected from the group consisting of (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, 4-acryloylmorpholine, tert-butylacrylamidosulfonic acid, and salts thereof are preferred, but the present invention is not limited thereto.
[0024] Specific examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters in which the alkyl group has 1 to 18 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. (meth)acrylic acid alkyl esters such as n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-pentyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, tridecyl (meth)acrylate, and n-stearyl (meth)acrylate; alicyclic (meth)acrylic acid esters such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and 1-adamantyl (meth)acrylate; 2-methoxyethyl (meth)acrylate alkoxy group-containing (meth)acrylic acid esters such as ethoxyethoxyethyl (meth)acrylate and methoxypolyethylene glycol (meth)acrylate such as methoxytriethylene glycol (meth)acrylate; hydroxyalkyl (meth)acrylates (wherein an aryl group may be bonded to the hydroxyalkyl group via an ether bond) such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate and 2-hydroxybutyl (meth)acrylate; glycerin mono(meth)acrylate; polyalkylene glycol mono(meth)acrylates such as polyethylene glycol mono(meth)acrylate and polyethylene glycol-polypropylene glycol copolymer; (meth)acrylic acid esters having an aromatic ring such as benzyl (meth)acrylate; and (meth)acrylic acid esters having a heterocyclic ring such as tetrahydrofurfuryl (meth)acrylate, but are not limited thereto.
[0025] The hydrogel may or may not contain acrylic acid as an acrylic monomer. When the hydrogel contains acrylic acid, the amount of acrylic acid in the hydrogel is preferably small, for example, 15% by mass or less, preferably 5% by mass or less, based on the hydrogel.
[0026] The amount of the monofunctional monomer added is preferably within a range of 98.5% by mass to 99.97% by mass relative to the total amount of the polymer matrix in terms of forming a hydrogel. Similarly, the content of the structural unit derived from the monofunctional monomer in the polymer matrix is preferably within a range of 98.5% by mass to 99.97% by mass.
[0027] The amount of the acrylic monomer added is preferably within a range of 98.5% to 99.98% by mass, and more preferably 99.5 to 99.85% by mass, based on the total amount of the polymer matrix in terms of forming a hydrogel. Similarly, the content of structural units derived from the acrylic monomer in the polymer matrix is preferably within a range of 98.5% to 99.98% by mass, and more preferably within a range of 99.5% to 99.85% by mass.
[0028] Furthermore, the amount of monofunctional monomer or acrylic monomer added is preferably within a range of 5% by mass to 50% by mass with respect to the hydrogel in terms of forming the hydrogel, resistance to tearing, and hardness. The content of monofunctional monomer or acrylic monomer in the hydrogel is preferably 2.0% by mass or more. In terms of allowing the movement of ions in the hydrogel, the content of monofunctional monomer or acrylic monomer in the hydrogel is preferably 60% by mass or less.
[0029] As the crosslinkable monomer, it is preferable to use a monomer having two or more polymerizable carbon-carbon double bonds in the molecule. Specifically, there can be mentioned polyfunctional (meth)acrylamides or polyfunctional (meth)acrylic acid esters such as methylene bis(meth)acrylamide, ethylene bis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, glycerin di(meth)acrylate, glycerin tri(meth)acrylate, tetraallyloxyethane, diallyl ammonium chloride, etc., which can be used alone or in combination of two or more. In addition, as the crosslinkable monomer having two or more polymerizable double bonds in the molecule, a polyglycerin derivative, which is a polyfunctional compound having two or more (meth)acryloyl groups or vinyl groups and a molecular weight of 400 or more, as described in Japanese Patent No. 2803886, can also be used. The above-mentioned polyfunctional (meth)acrylamides, the above-mentioned polyfunctional (meth)acrylic acid esters, and polyglycerin derivatives are included in the acrylic monomers.
[0030] The amount of the crosslinkable monomer added is preferably within the range of 0.020% by mass to 1.5% by mass, more preferably 0.15% by mass to 0.50% by mass, based on the total amount of the polymer matrix, in terms of adhesion and hardness. When the amount of the crosslinkable monomer added is 0.020% by mass or more, the crosslink density is maintained, the shape stability is good, and at the same time, the adhesion can be sufficiently increased. When the amount of the crosslinkable monomer added is 1.5% by mass or less, the adhesion and / or repeated adhesion can be maintained high, and a soft gel can be obtained. Similarly, the content of the structural unit derived from the crosslinkable monomer in the polymer matrix is preferably within the range of 0.020% by mass to 1.5% by mass, more preferably 0.15% by mass to 0.50% by mass.
[0031] Furthermore, the amount of the crosslinkable monomer added is preferably within a range of 0.010% by mass to 0.10% by mass with respect to the hydrogel in terms of the adhesive strength, handling properties, etc. of the gel or gel sheet. Similarly, the content of structural units derived from the crosslinkable monomer in the hydrogel is preferably within a range of 0.010% by mass to 0.10% by mass.
[0032] From the standpoint of adhesion and hardness, it is preferable that the amount of the acrylic monomer added as a constituent monomer of the polymer matrix is within the range of 98.5% by mass to 99.97% by mass and the amount of the crosslinkable monomer added is within the range of 0.030% by mass to 1.5% by mass, relative to the total amount of the polymer matrix, and it is more preferable that the amount of the acrylic monomer added is within the range of 99.5% by mass to 99.85% by mass and the amount of the crosslinkable monomer added is within the range of 0.15% by mass to 0.50% by mass.
[0033] From the standpoint of adhesion and hardness, it is preferable that the content of structural units derived from acrylic monomers in the polymer matrix is within the range of 98.5% by mass to 99.97% by mass and the content of structural units derived from crosslinkable monomers is within the range of 0.030% by mass to 1.5% by mass, and it is more preferable that the content of structural units derived from acrylic monomers in the polymer matrix is within the range of 99.5% by mass to 99.85% by mass and the content of structural units derived from crosslinkable monomers is within the range of 0.15% by mass to 0.50% by mass.
[0034] The copolymer of an acrylic monomer and a crosslinkable monomer preferably does not contain any additional monomer constituting the copolymer other than the acrylic monomer and the crosslinkable monomer, but may contain such an additional monomer.
[0035] The hydrogel of the present embodiment further contains water. The water content in the hydrogel is not particularly limited, but is preferably 10 to 60% by mass, more preferably 10 to 45% by mass, and even more preferably 15 to 30% by mass, relative to the hydrogel. When the water content is 10% by mass or more, the water content relative to the equilibrium water content of the hydrogel is sufficient. When the water content is 60% by mass or less, the hydrogel is less likely to shrink or change in physical properties due to drying.
[0036] The hydrogel of the present embodiment further contains a polyhydric alcohol. The polyhydric alcohol is added to impart wettability to the hydrogel. The polyhydric alcohol is not particularly limited, and examples thereof include diols such as ethylene glycol, triethylene glycol, 1,6-hexanediol, 1,9-nonanediol, propylene glycol, butanediol, trihydric or higher polyhydric alcohols such as glycerin, pentaerythritol, sorbitol, polyhydric alcohol condensates such as polyethylene glycol, polypropylene glycol, polyglycerin, and polyhydric alcohol denaturants such as polyoxyethylene glycerin.
[0037] Among polyhydric alcohols, it is preferable to use polyhydric alcohols that are liquid in the temperature range in which the hydrogel is used (for example, around 20°C when used indoors), and specifically, one or more selected from the group consisting of ethylene glycol, triethylene glycol, propylene glycol, polypropylene glycol, polyethylene glycol, polyglycerin, and glycerin are preferred.
[0038] The content of polyhydric alcohol in the hydrogel is not particularly limited, but is preferably within the range of 20 to 70% by mass, more preferably within the range of 25 to 65% by mass, relative to the hydrogel. The content of polyhydric alcohol is preferably greater than the content of water, but may be less than the content of water. When the content of polyhydric alcohol is 20% by mass or more, it is advantageous in terms of the moisturizing power, flexibility, and stability over time of the hydrogel. In addition, when the content of polyhydric alcohol is 70% by mass or less, it is generally an amount of polyhydric alcohol that can be retained by a polymer matrix, and is also advantageous in terms of sufficient adhesion of the hydrogel.
[0039] The hydrogel according to the embodiment of the present invention further contains an electrolyte, which can impart electrical conductivity to the hydrogel.
[0040] The electrolyte is not particularly limited, and for example, hypochlorite, chlorite, chlorate, perchlorate, hydrochloride, sulfate, carbonate, nitrate, and phosphate of various metals are preferably used. Preferred examples of such metal salts include metal chlorides with low skin irritation such as sodium chloride, potassium chloride, and magnesium chloride, but are not limited thereto. In addition, metal halides such as alkaline earth metal halides can also be used as the electrolyte. Furthermore, inorganic salts such as ammonium salts and various complex salts; salts of monovalent organic carboxylic acids such as acetic acid, benzoic acid, and lactic acid; salts of polyvalent organic carboxylic acids such as tartaric acid; monovalent or divalent or higher salts of polyvalent carboxylic acids such as phthalic acid, succinic acid, adipic acid, and citric acid; metal salts of organic acids such as sulfonic acid and amino acids; organic ammonium salts, etc. can also be used as the electrolyte.
[0041] When imparting electrical conductivity to the hydrogel, the content of the electrolyte in the hydrogel is preferably 0.050 to 10 mass % relative to the hydrogel, and more preferably 0.10 to 6.0 mass %. From the viewpoint of electrical conductivity, the content of the electrolyte is preferably 0.050 mass % or more. Moreover, if the content of the electrolyte is too high, waste occurs in terms of costs, so the content is preferably 10 mass %.
[0042] The hydrogel of the present embodiment may also contain a pH adjuster for the purpose of adjusting the pH, such as a base such as sodium hydroxide.
[0043] Additionally, the hydrogels of the present embodiments may optionally contain molecules such as polyacrylic acid or salts thereof to enhance adhesion.
[0044] The hydrogel according to the embodiment of the present invention may contain other additives as necessary, such as rust inhibitors, antifungal agents, antioxidants, defoamers, stabilizers, surfactants, colorants, etc.
[0045] The thickness of the hydrogel according to the embodiment of the present invention is not particularly limited, but is preferably 0.60 mm to 3.0 mm.
[0046] A preferred embodiment of the hydrogel of the present invention is a direct current hydrogel which comprises a polymer matrix, water, a polyhydric alcohol, an electrolyte, and a clay mineral, wherein the polymer matrix is a copolymer of one or more monofunctional monomers selected from a (meth)acrylamide monomer and a (meth)acrylic acid ester, and a crosslinkable monomer, and which exhibits a voltage change rate of 10% or less when a direct current of 2 mA is applied for 15 minutes.
[0047] The hydrogel having such a configuration can be a hydrogel for applying direct current, which shows little change in voltage value when a direct current is applied for a certain period of time. The thickness of the hydrogel for applying direct current is not particularly limited, but is preferably 0.60 mm to 3.0 mm.
[0048] In the hydrogel according to the embodiment of the present invention, when a direct current (constant current) of 2 mA is applied to a hydrogel having a diameter of 30 mm for 15 minutes, the voltage change rate is 10% or less. In the hydrogel according to the embodiment of the present invention, the voltage change caused by the direct current is unlikely to occur. The voltage change rate is calculated by {(voltage 15 minutes after the start of application of direct current)-(voltage immediately after application of direct current)} / (voltage immediately after application of direct current)}×100.
[0049] In a particular embodiment, the hydrogel is a hydrogel sheet having a thickness in the range of 1.0 mm to 3.0 mm, and a voltage change rate of 10% or less when a direct current of 2 mA is applied for 15 minutes.
[0050] In addition, the hydrogel according to the embodiment of the present invention preferably has a resistance change rate of 10% or less when a direct current of 2 mA is applied for 15 minutes. The hydrogel according to the embodiment of the present invention is unlikely to undergo a change in resistance due to a direct current. The rate of resistance change is calculated by {(resistance 15 minutes after the start of application of direct current)-(resistance immediately after application of direct current)} / (resistance immediately after application of direct current)×100.
[0051] How the hydrogel is produced The hydrogel can be obtained by polymerizing and crosslinking a mixture liquid (hereinafter also referred to as a composition for forming a hydrogel for application of a direct current) in which the above-mentioned materials other than water and a polymerization initiator are uniformly dispersed in water, by heating or irradiating with ultraviolet light, etc. Dispersion includes not only a state in which a solute is dispersed in water without being mixed with water, but also a dissolution in which a solute is mixed with water to form a mixture of a uniform phase.
[0052] The components (clay mineral, acrylic monomer, crosslinkable monomer, water, polyhydric alcohol, electrolyte, etc.) in the hydrogel-forming composition for application of direct current and the preferred contents thereof are as described above for the hydrogel.
[0053] The polymerization initiator may be a thermal polymerization initiator, a photopolymerization initiator, or an oxidation-reduction initiator, and a known thermal polymerization initiator or photopolymerization initiator for polymerizing an acrylic monomer can be used. The content of the polymerization initiator is not particularly limited, but is preferably 0.010% by mass or more and 1.0% by mass or less relative to the mixture liquid (composition for forming a hydrogel for application of direct current) before polymerization excluding the polymerization initiator.
[0054] When polymerization is performed by ultraviolet irradiation, the amount of ultraviolet irradiation is not particularly limited, but the peak intensity is preferably 50 to 150 mW / cm 2 It is preferable to irradiate the substrate with ultraviolet light having a peak intensity of 50 mW / cm 2 Above this level, the adhesive function improves due to the increase in low molecular weight components in the hydrogel, and the viscoelasticity is 150 mW / cm 2 If the concentration is less than 800 mJ / cm, it is easy to obtain a suitable molecular weight component. The cumulative dose of ultraviolet light varies depending on the content of the polymerization initiator, etc., but is, for example, 800 mJ / cm 2 ~10000mJ / cm 2 and preferably in the range of 2000 mJ / cm 2 ~10000mJ / cm 2 It is more preferable that the range is within the range.
[0055] In a preferred embodiment, the method for producing a hydrogel for applying a direct current comprises the steps of: producing a hydrogel having a peak intensity of 50 to 150 mW / cm for a mixture liquid containing an acrylic monomer, a crosslinkable monomer, water, a polyhydric alcohol, an electrolyte, and a clay mineral; 2 The method is characterized by comprising a step of irradiating the substrate with ultraviolet light.
[0056] Hydrogel Sheet The hydrogel for applying a direct current according to the embodiment of the present invention can be formed into a desired shape such as a sheet by pouring a mixture liquid (a composition for forming a hydrogel for applying a direct current) before polymerization into a container of a desired shape such as a bottomed container having a substantially rectangular cross section, and polymerizing the mixture by irradiation with ultraviolet light or the like. Hereinafter, the sheet-shaped hydrogel will be referred to as a "hydrogel sheet" or simply as a "gel sheet". The shape of the hydrogel sheet can be any shape depending on the purpose, and examples thereof include, but are not limited to, a substantially rectangular shape, a substantially circular shape, and the like.
[0057] If the thickness of the hydrogel sheet for applying direct current according to the embodiment of the present invention is too thick, the shear stress decreases, and if it is too thin, the cohesive force decreases. In addition, the smaller the thickness of the hydrogel sheet for applying direct current, the greater the voltage change rate. Taking these factors into consideration, a person skilled in the art can select an appropriate thickness. The thickness of the hydrogel sheet for applying direct current is preferably 0.6 mm to 3.0 mm, and more preferably 1.0 mm to 3.0 mm.
[0058] The hydrogel sheet for applying a direct current according to an embodiment of the present invention may include an intermediate substrate. Such intermediate substrates are used in the art for the purpose of reinforcing the hydrogel sheet and / or improving the shape retention. The intermediate substrate is preferably embedded in the hydrogel so as to extend in a direction substantially parallel to a plane perpendicular to the thickness direction of the hydrogel. As a specific embodiment of the intermediate substrate, it may be made of a nonwoven fabric or a woven fabric. Examples of materials for the nonwoven fabric and the woven fabric include natural fibers such as cellulose, silk, and hemp, synthetic fibers such as polyester, nylon, rayon, polyethylene, polypropylene, and polyurethane, and blends thereof. The intermediate substrate may contain a binder as necessary. The intermediate substrate may also be colored as necessary.
[0059] The thickness of the intermediate substrate is not particularly limited, but is preferably 0.050 mm to 2.0 mm in terms of electrical conductivity and reinforcement of the hydrogel sheet.
[0060] A base film may be disposed on the surface of the hydrogel sheet for applying a direct current according to the embodiment of the present invention. The base film is preferably disposed so as to cover the entire surface of the hydrogel sheet that faces the base film.
[0061] As the base film, for example, a resin film made of a resin such as polyester, polyolefin, polystyrene, or polyurethane, paper, or paper laminated with the above-mentioned resin film can be used.
[0062] The surface of the base film that contacts the hydrogel sheet is preferably subjected to a release treatment. Examples of the release treatment include silicone coating, and in particular, a baked silicone coating that crosslinks and hardens with heat or ultraviolet light is preferred. As the film to be subjected to the release treatment, a biaxially stretched PET (polyethylene terephthalate) film, an OPP (oriented polypropylene) film, etc. are particularly preferred.
[0063] A top film may be placed on the surface of the hydrogel sheet for applying a direct current according to the embodiment of the present invention. The top film may be made of the same material as the base film. For example, when a top film is placed on the hydrogel sheet and then irradiated with ultraviolet light or the like to cause polymerization, it is preferable to select a film made of a material that does not block light so as not to interfere with photopolymerization.
[0064] A top film may be placed on one surface of the hydrogel sheet for applying a direct current according to an embodiment of the present invention, and a base film may be placed on the other surface of the hydrogel sheet for applying a direct current according to an embodiment of the present invention.
[0065] The hydrogel for applying direct current (including hydrogel sheet) according to the embodiment of the present invention is unlikely to cause a change in voltage even when a direct current is applied for a certain period of time. Therefore, the hydrogel according to the embodiment of the present invention can be used as a medical electrode hydrogel. Preferably, the hydrogel can be used as a medical electrode hydrogel that is disposed between an electrode made of a conductive material and the skin surface. The hydrogel for applying direct current (including hydrogel sheet) according to the embodiment of the present invention can be used as a component of an electrode pad having a hydrogel for applying direct current and an electrode electrically connected to the hydrogel for applying direct current.
[0066] The electrode pad can be applied to the electrode portion of various devices, for example, medical devices such as a biomedical measuring device or a bioelectrical treatment device, or industrial measuring devices such as measuring devices for inspecting the surface of ground or rock, and devices for detecting damage to water-leaking sheets at waste disposal sites, etc. In a preferred embodiment, the electrode pad is a biomedical electrode pad that can be applied to medical devices such as a biomedical measuring device or a bioelectrical treatment device.
[0067] Specific embodiments of the hydrogel sheet for applying direct current and the electrode pad of the present invention are described below.
[0068] 1 is a schematic cross-sectional view of a hydrogel sheet according to one embodiment of the present invention. The hydrogel sheet 1 includes a hydrogel sheet layer 10 made of the hydrogel sheet according to the embodiment of the present invention, a base film 12 arranged on one side of the hydrogel sheet layer 10 in contact with the hydrogel sheet layer 10, and a top film 13 arranged on the opposite side of the hydrogel sheet layer 10 to the side on which the base film 12 is arranged in contact with the hydrogel sheet 10. The details of the hydrogel sheet layer 10, the base film 12, and the top film 13 are as described above. The base film 12 and / or the top film 13 may be omitted.
[0069] Fig. 2 is a schematic cross-sectional view of a hydrogel sheet according to another embodiment of the present invention. Compared to the hydrogel sheet 1 in Fig. 1, the hydrogel sheet 1 in Fig. 2 includes an intermediate substrate 11 embedded in a hydrogel sheet layer 10. The details of the intermediate substrate 11 are as described above.
[0070] 3 is a schematic cross-sectional view of an electrode pad comprising a hydrogel sheet according to one embodiment of the present invention. The electrode pad 2 comprises a hydrogel sheet layer 10 made of the hydrogel sheet according to one embodiment of the present invention, and an electrode 20 electrically connected to the hydrogel sheet layer 10. A support substrate 15 is disposed on the surface of the hydrogel sheet layer 10 in contact with the hydrogel sheet layer 10. The electrode 20 extends into the hydrogel sheet layer 10 by penetrating the support substrate 15.
[0071] A general insulating resin can be used as the supporting substrate 15. The supporting substrate 15 is preferably a film, foam, or nonwoven fabric containing, for example, polyester, polyethylene, polypropylene, polyvinyl chloride, polyethylene terephthalate (PET), polyurethane, silicone, or a combination of two or more of these resins, or rubber. The thickness of the supporting substrate 15 is preferably 10 to 500 μm.
[0072] The electrode 20 can usually be obtained using a predetermined conductive material. Examples of such conductive materials include conductive pastes prepared by using metals such as nickel, molybdenum, stainless steel, silver, or platinum, metal mixtures such as silver or silver-silver chloride, or materials such as carbon black or graphite, either alone or in combination. The electrode 20 can be obtained, for example, by printing a conductive paste on the surface of the support base material 15 described above to form a conductive layer of the electrode. Alternatively, the electrode 20 can be obtained by coating the surface of a resin molded product, such as an ABS resin molded product, with a conductive ink containing the conductive material described above. Alternatively, the electrode 20 can be obtained by laminating the support base material 15 described above with a metal foil such as silver, aluminum, or tin, or a film containing the conductive material described above.
[0073] The electrode pad 2 can be attached to the surface of the adherend 30 along the shape thereof via the surface of the hydrogel sheet layer 10. The electrode pad 2 is preferably a biological electrode pad. The surface 30 of the adherend is preferably the surface of human skin. With such an electrode pad 2, voltage changes are suppressed even when a direct current is applied for a certain period of time.
[0074] 4 is a schematic cross-sectional view of another electrode pad comprising the hydrogel sheet of one embodiment of the present invention. The electrode pad 2 comprises a hydrogel sheet layer 10 made of the hydrogel sheet of one embodiment of the present invention, an electrode 20 disposed on the surface of the hydrogel sheet layer 10 in contact with the hydrogel sheet layer 10, and a support substrate 15 disposed in contact with the surface of the electrode 20 opposite to the side in contact with the hydrogel sheet layer 10.
[0075] The electrode pad 2 can be attached to the surface 30 of the adherend through the surface of the hydrogel sheet layer 10, following the shape of the adherend. The adherend surface 30 is preferably the surface of human skin. With such an electrode pad 2, even if a direct current is applied for a certain period of time, a change in voltage is suppressed. EXAMPLES
[0076] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to these examples.
[0077] 1. Hydrogel Preparation (1) Preparation of monomer mixture Using a stirring / mixing vessel, 20% by mass of acrylamide as a non-crosslinking monomer, 0.060% by mass of N,N'-methylenebisacrylamide as a crosslinking monomer, 1.0% by mass of zeolite (A-type zeolite, TSC, Mizusawa Chemical Industries, Ltd.) as a zeolite clay mineral, 18% by mass of ion-exchanged water, and 56% by mass of glycerin as a moisturizing agent were added and uniformly dispersed, as shown in the table. Next, 2.0% by mass of sodium chloride as an electrolyte, and 2.94% by mass of sodium citrate, sodium benzoate, polyacrylic acid, and a photopolymerization initiator as other additives were added, and the mixture was stirred until completely dissolved, to obtain a monomer blend liquid.
[0078] (2) Manufacturing of hydrogel sheets Example 1 The obtained mixture was poured into a silicone resin mold and spread evenly to a thickness of 3.0 mm. Then, a metal halide lamp was used to apply a peak irradiance of 130 mW / cm. 2 , energy amount 3000mJ / cm 2 By irradiating the sheet with ultraviolet light at 600 nm, a hydrogel sheet having a thickness of 3.0 mm was obtained.
[0079] (Examples 2 to 9) A hydrogel sheet was obtained in the same manner as in Example 1, except that the type or amount of zeolite added was changed as shown in Table 1. Zeolites 5AP, EX122, MT-100, MT-8000, CPT-3, and Y-400 used in Examples 2 to 7 were all obtained from Mizusawa Chemical Industries, Ltd.
[0080] Example 10 A hydrogel sheet was obtained in the same manner as in Example 1, except that the thickness was changed as shown in Table 1.
[0081] Example 11 Using a stirring / mixing vessel, as shown in the table, 14 mass% acrylic acid as a monofunctional monomer, 10 mass% tert-butylacrylamidosulfonic acid (TBAS), 0.060 mass% N,N'-methylenebisacrylamide as a crosslinking monomer, and 8.0 mass% 50 mass% NaOH solution were added to adjust the pH to 4-5. Then, 13 mass% ion-exchanged water and 49 mass% glycerin as a moisturizing agent were added and stirred until completely dissolved. Next, 2.0 mass% sodium chloride as an electrolyte, and 2.94 mass% of citric acid, sodium benzoate, photopolymerization initiator, and surfactant as other additives were added and stirred until completely dissolved to obtain a polymerization solution. Using the polymerization solution, a hydrogel was obtained in the same manner as in Example 1.
[0082] Example 12 As shown in Table 1, a hydrogel sheet was obtained in the same manner as in Example 1, except that the clay mineral was changed to "allophane, manufactured by Shinagawa General Co., Ltd., Sekado P-1."
[0083] Example 13 Hydrogel sheets were obtained in the same manner as in Example 1, except that the amount of allophane added was changed as shown in Table 1.
[0084] Example 14 As shown in Table 1, a hydrogel sheet was obtained in the same manner as in Example 1, except that the clay mineral was changed to "hydrotalcite, manufactured by Toda Kogyo Co., Ltd., LT-015D."
[0085] Example 15 A hydrogel sheet was obtained in the same manner as in Example 1, except that the amount of hydrotalcite added was changed as shown in Table 1.
[0086] (Comparative Examples 1 to 5) As shown in Table 1, except for changing the amount and thickness of the additive, hydrogel sheets were obtained in the same manner as in Examples 1 and 11. At this time, in Comparative Example 4, a gel could not be produced (ultraviolet rays did not penetrate deep into the gel, and it remained uncured).
[0087] 2.Measurement method The obtained hydrogels of Examples 1 to 15 and Comparative Examples 1 to 5 were evaluated for each of the following items.
[0088] (1) Voltage value evaluation A hydrogel sheet of the Example or Comparative Example cut to 30 mmφ was sandwiched between two SUS plates, and two of these were prepared as test materials. One test material was connected to the positive electrode side of a DC stabilized power supply, and the other test material was connected to the negative electrode side, and a resistor of 1 kΩ was connected between the test materials. In the circuit, the resistor simulates the adherend surface, for example, skin. A DC current was applied to the circuit under conditions of a constant current of 2 mA and an application time of 15 minutes. The initial voltage value was taken 5 seconds after the current application, and the voltage value after 15 minutes was compared to determine the rate of change. A rate of change of 10% or less was marked as ◯, and a rate of change of more than 10% was marked as ×.
[0089] (2) Resistance value evaluation A hydrogel sheet of the Example or Comparative Example cut to 30 mmφ was sandwiched between two SUS plates, and two of these were prepared as test materials. One test material was connected to the positive electrode side of a DC stabilized power supply, and the other test material was connected to the negative electrode side, and a 1 kΩ resistor was connected between the test materials. In the circuit, the resistor simulates the adherend surface, for example, skin. A DC current was applied to the circuit under conditions of a constant current of 2 mA and an application time of 15 minutes. The resistance of the circuit was measured, and it was judged as ◯ when the resistance did not change (change rate of 10% or less), and × when it changed (change rate of more than 10%).
[0090] From the above results, it was shown that the hydrogel of this example suppressed the voltage change and resistance change due to the application of direct current for a certain period of time. In addition, in the comparative example in which the voltage change rate exceeded 10%, problems occurred such as exceeding the output control range of the device and being unable to pass a constant current due to the promotion of electrolysis of water in the hydrogel. [Table 1] [Table 2] [Explanation of symbols]
[0091] 1...hydrogel sheet, 2...electrode pad.
Claims
1. A hydrogel for applying direct current, which contains a clay mineral, and has a voltage change rate of 10% or less when a direct current of 2 mA is applied to it for 15 minutes.
2. The hydrogel according to claim 1, wherein the content of the clay mineral is 0.60 to 15.0 parts by mass per 100 parts by mass of the hydrogel.
3. 2. The hydrogel for application of direct current according to claim 1, wherein the clay mineral is an inorganic substance having ion exchange ability.
4. 4. The hydrogel for applying a direct current according to claim 3, wherein the inorganic material having an ion exchange capacity is zeolite.
5. 2. The hydrogel according to claim 1, having a thickness of 0.60 mm to 3.0 mm.
6. 2. The hydrogel for applying direct current according to claim 1, wherein the hydrogel comprises a polymer matrix, water, a polyhydric alcohol, and an electrolyte, and the polymer matrix is a copolymer of one or more monofunctional monomers selected from a (meth)acrylamide-based monomer and a (meth)acrylic acid ester, and a crosslinkable monomer.
7. A hydrogel sheet for applying direct current, which is obtained by molding the hydrogel for applying direct current according to any one of claims 1 to 6.
8. The hydrogel sheet for applying direct current according to claim 6, having a thickness of 0.60 mm to 3.0 mm.
9. A medical electrode used by being placed between an electrode element made of a conductive material and a skin surface, the medical electrode comprising the hydrogel for applying direct current according to any one of claims 1 to 5.
10. A biological electrode pad comprising the hydrogel sheet for applying direct current according to claim 7 and an electrode element electrically connected to the hydrogel sheet for applying direct current.
11. A method for producing a hydrogel for applying direct current according to any one of claims 1 to 6, comprising the step of irradiating a polymerizable solution containing an acrylic monomer, a crosslinkable monomer, water, a polyhydric alcohol, an electrolyte, and a clay mineral with ultraviolet light having a peak intensity of 50 to 150 mW / cm2.
12. A hydrogel-forming composition for application of direct current, comprising an acrylic monomer, a crosslinkable monomer, water, a polyhydric alcohol, an electrolyte, and a clay mineral.
Citation Information
Patent Citations
EEG measurement and brain stimulation system
JP2017502722A
Conductive laminated hydrogel sheet
JP2018051155A